2022
DOI: 10.1038/s41598-022-20869-2
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific hearing-in-noise performance is associated with absolute pitch proficiency

Abstract: Recent evidence suggests that musicians may have an advantage over non-musicians in perceiving speech against noisy backgrounds. Previously, musicians have been compared as a homogenous group, despite demonstrated heterogeneity, which may contribute to discrepancies between studies. Here, we investigated whether “quasi”-absolute pitch (AP) proficiency, viewed as a general trait that varies across a spectrum, accounts for the musician advantage in hearing-in-noise (HIN) performance, irrespective of whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Turning to music training and speech-in-noise perception, no musicianship advantage was observed in line with several previous studies (Boebinger et al 2015 ; Hsieh et al 2022 ; Madsen et al 2017 , 2019 ; Ruggles et al 2014 ; Yeend et al 2017 ). Inevitably, there is some variation in the design of previous studies that have (Meha-Bettison et al 2018 ; Parbery-Clark et al 2009a , b ; Slater et al 2015 ) or have not (Boebinger et al 2015 ; Madsen et al 2017 , 2019 ; Ruggles et al 2014 ; Yeend et al 2017 ) found differences between musicians and non-musicians in this regard.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Turning to music training and speech-in-noise perception, no musicianship advantage was observed in line with several previous studies (Boebinger et al 2015 ; Hsieh et al 2022 ; Madsen et al 2017 , 2019 ; Ruggles et al 2014 ; Yeend et al 2017 ). Inevitably, there is some variation in the design of previous studies that have (Meha-Bettison et al 2018 ; Parbery-Clark et al 2009a , b ; Slater et al 2015 ) or have not (Boebinger et al 2015 ; Madsen et al 2017 , 2019 ; Ruggles et al 2014 ; Yeend et al 2017 ) found differences between musicians and non-musicians in this regard.…”
Section: Discussionsupporting
confidence: 89%
“…A similar finding was reported in a longitudinal study also using HINT (Slater et al 2015 ) and another study using a different design (Meha-Bettison et al 2018 ). However, many other studies have failed to replicate a musicianship advantage for speech perception in noise (Boebinger et al 2015 ; Hsieh et al 2022 ; Madsen et al 2017 , 2019 ; Ruggles et al 2014 ; Yeend et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%